2018
DOI: 10.1021/acs.jpcc.8b04921
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfers at a Dopamine-Functionalized TiO2 Interface

Abstract: Despite the many successful syntheses and applications of dopamine-functionalized TiO 2 nanohybrids, there has not yet been an atomistic understanding of the interaction of this 1,2-dihydroxybenzene derivative ligand with the titanium dioxide surfaces. In this work, on the basis of a wide set of dispersion-corrected hybrid density functional theory (DFT) calculations and density functional tight binding (DFTB) molecular dynamics simulations, we present a detailed study of the adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…41,42 The most relevant biomedical applications of TiO 2 is in photodynamic therapy for cancer treatment, [43][44][45][46] being an excellent ROS (reactive oxygen species) generator under light irradiation, but it could also be used as a drug delivery system, 46 for cell imaging, [47][48][49] biosensors, antimicrobial and bactericidal action and genetic engineering. 41,50 In previous studies, 51,52 we have shown and discussed why curved TiO 2 nanoparticles are more suitable than flat (101) TiO 2 surfaces for biomedical applications, in agreement with experimental results. 42 The main reasons are that curved NPs expose many low coordinated sites 53 that can strongly anchor functionalizing linkers and that the high density of linkers on curved NPs prevents their bending towards the surface, which makes them more available for tethering bioactive molecules.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…41,42 The most relevant biomedical applications of TiO 2 is in photodynamic therapy for cancer treatment, [43][44][45][46] being an excellent ROS (reactive oxygen species) generator under light irradiation, but it could also be used as a drug delivery system, 46 for cell imaging, [47][48][49] biosensors, antimicrobial and bactericidal action and genetic engineering. 41,50 In previous studies, 51,52 we have shown and discussed why curved TiO 2 nanoparticles are more suitable than flat (101) TiO 2 surfaces for biomedical applications, in agreement with experimental results. 42 The main reasons are that curved NPs expose many low coordinated sites 53 that can strongly anchor functionalizing linkers and that the high density of linkers on curved NPs prevents their bending towards the surface, which makes them more available for tethering bioactive molecules.…”
Section: Introductionsupporting
confidence: 80%
“…In a previous study, we extensively investigated the adsorption modes of dopamine on the surface of this TiO 2 nanoparticle. 51,52 We have shown that while the bidentate catechol portion of dopamine binds to the oxide surface through coordinate bonds, in agreement with infrared studies, 54,58 the primary amine could remain exposed to the surrounding environment providing a hook to tether biomolecules or drugs (DOX here). However, we also showed that, especially at low coverage, the molecule could bend towards the NP and establish either a hydrogen or a coordinate bond with the surface atoms.…”
Section: Dox Loaded On Dopamine-functionalized Tio 2 Nanoparticlessupporting
confidence: 70%
“…This method has already been applied successfully to investigate adsorbed molecules on titanium oxides. [24][25][26] The details about the DFTB method and its derivation can be found in ref. 14, 27 and 28. For all the SCC-DFTB calculations we used the DFTB+ 18.2 open-source package.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The proton transfer at a dopamine-functionalized TiO 2 interface was investigated by using dispersion-corrected hybrid DFT calculations and DFT tight-binding (DFTB) MD simulations [204]. The adsorption modes, patterns of growth, and configurations of dopamine on the anatase (101) TiO 2 surface were considered with reference to the binding archetype of catechol.…”
Section: Figure 28mentioning
confidence: 99%